The effects of lowering barometric pressure on pain behavior and the stress hormone in mice with neuropathic pain - Yuki Terajima; Jun Sato; Hideaki Inagaki; Takahiro Ushida (PLoS ONE, 2025)
Background Lowering barometric pressure (LP) can exacerbate neuropathic pain. However, animal studies in this field are limited to a few conditions. Furthermore, although sympathetic involvement has been reported as a possible mechanism, whether the sympathetic nervous system is involved in the hypothalamic-pituitary-adrenal (HPA) axis remains unknown. To address these issues, we investigated LP-induced hyperalgesia by focusing on the cumulative effect of LP and measuring plasma corticosterone levels as a marker of HPA axis activation in mice. Methods Mice with chronic constriction injury (CCI) were used in this study. For behavioral tests, two types of LP stimulation were adopted: a single LP at 20 hPa (Single LP) and three consecutive LPs at 20 hPa (3LPs). Twelve mice were used for each protocol. The no-pressure-change protocol was used as the control. The mechanical sensitivity was tested before and after LP stimulation using von Frey filaments (vF). For corticosterone measurements, six CCI and six intact mice were exposed to 3LPs (CCI-3LPs and INT-3LPs), and another six CCI and six intact mice were exposed to the no-pressure-change protocol (CCI-NP and INT-NP). Blood samples were collected immediately after exposure. Plasma corticosterone levels were measured by ELISA. Results The number of paw elevations by vF before and after LP stimulation did not differ significantly in either the Single LP or the no-pressure-change protocol. For the 3LPs, the number of paw elevations after LP stimulation was significantly greater than before stimulation. Plasma corticosterone levels in the CCI-3LPs were significantly higher than those in CCI-NPs. In intact mice, there was no significant difference in plasma corticosterone levels between the INT-3LPs and INT-NPs. Conclusions LP has a cumulative effect on neuropathic pain. Hypothalamic-pituitary-adrenal axis activation may have an important relationship with LP-induced pain in mice.